Rural Society and Barriers to Well-Being - Edwards, Wayne; Natarajan, Tara (Journal of Northern Studies, 2010)
Service availability, access, and delivery are universal problems every society faces. Invariably, some members of any society are unable to access all of the services they need. This article identifies crucial factors that create service access barriers by using a modified Social Fabric Matrix (SFM) methodology. The components of the matrix go to the core of the question of well-being and are ideally suited to clarifying access rigidities. The primary result of the described research is that, while measures of service access rigidities are broadly consistent with other measures in explaining geographical variation in well-being, access rigidity measures also reveal differences not seen in other analyses.